Factors associated with the need for intraoperative packed red cells transfusion in pediatric liver transplant patients - Kapuangan, Christopher; Utariani, Arie; Hanindito, Elizeus (DiscoverSys Inc., 2019)
Background: Massive hemorrhage is one of the most common problems encountered during a liver transplantation procedure. Correction of the blood loss using packed red cells (PRC) is essential during the procedure to improve outcome. This retrospective study aims to investigate preoperative and intraoperative factors that may predict the PRC need.Materials and Methods: Thirty-four patients who underwent pediatric liver transplantation procedure within 2010-2018 were included in this study. Their medical record was examined and the data was analyzed using a comparison of mean and regression model.Results: The mean bleeding in this study was found to be 906.62±674.30 mL, while the mean PRC transfusion was 566.71±307.30 mL. Correction of blood loss was also compensated with other means such as a crystalloid or colloid fluid.Conclusion: This study statistically demonstrated that pre-operative weight, as well as bleeding volume, significantly affect the PRC transfusion requirement (p <0.05). However, other factors such as hemoglobin and surgical duration may also be clinically significant factors to predict PRC transfusion need.